Auseinandergeschnittener Kontaktabzug Shango-Performance der Yoruba (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2013)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Photographs; Dance; Yoruba (African people); Yoruba (African people)--Religion; Ritual; Orisha religion; Albums; Shango; Yoruba Art; Orisha; Orisha Art; Yoruba Rituals; Yoruba Rites; Yoruba Ceremony